Development of clove extract-fortified functional yoghurt powder using spray: drying - Abdul Kalam Saleena, Lejaniya; Yusof, Yus Aniza; Song, Adelene Ai-Lian; In, Lionel Lian Aun; Nyam, Kar Lin; Pui, Liew Phing (Springer, 2024)
Spray-drying transforms functional yogurt into yogurt powder quickly and efficiently, maintaining product quality and enhancing storage stability. This process also adds value to the product. The study aimed to develop spray dried functional yoghurt powder encapsulating probiotics (Streptococcus thermophilus (S. thermophilus), Lactobacillus bulgaricus (L. bulgaricus), and Lactococcus lactis (L. lactis)) with longer shelf life. The production of functional yoghurt powder was optimized with Box–Behnken design using independent variables inlet air temperature (110–170 °C), feed temperature (10–20 °C), and pump speed (10–20). The optimum functional yoghurt powder was obtained at 164.04 (164) °C inlet air temperature, 20 °C feed temperature, and 10.72 (11) pump speed, respectively. The functional yoghurt powder with amorphous nature had storage viability (log CFU g−1) of 8.88 ± 0.03, 6.71 ± 0.12 and 8.16 ± 0.10 for S. thermophilus, L. bulgaricus, and L. lactis correspondingly on 49th day at 4 °C. The functional yoghurt powder demonstrated antibacterial activity, resulting in inhibition zones measuring approximately 18.33 ± 1.15 mm and 11.00 ± 0.00 mm against Klebsiella pneumoniae and Pseudomonas aeruginosa, respectively. Functional yoghurt powder had water activity 0.35–0.52, moisture content 7.27–16.22 (), process yield 2.29–5.33 (), hygroscopicity 10.09–16.87 (g/100 g) and degree of caking as 37.46–59.02 (). The bulk densities, tapped densities, particle density and porosity of yoghurt powder ranged from 242 to 425 (kg m−3), 301.9–485.7 (kg m−3), 1050–2500 (kg m−3), and 58.67–87.85 () respectively. Furthermore, the solubility, dispersibility, and wettability of the powder ranged from 33 to 60, 46.86–86.37, and 2.13–4.28 min, respectively. The current study successfully achieved optimization at an inlet temperature of 164.04 °C (164 °C), a feed temperature of 20 °C, and a pump speed of 10.72 (11), with desirability of 72.6. This study makes a substantial advancement in the production of probiotic yoghurt powder infused with clove, achieving the recommended levels of viability, shelf life, powder characteristics, reconstitution capability, and antibacterial effects. Moreover, the spherical morphology of the functional yoghurt powder was revealed through scanning electron microscopy.